Perilaku Partisipasi Pemilih pada Pemilihan Kepala Daerah Kabupaten Kudus Tahun 2018 - Mas'udi Mas'udi; Umi Qodarsasi; Nevy Rusmarina Dewi; Kastoro, Widiarsih (JSW (Jurnal Sosiologi Walisongo), 2018)
The high voter's participation in the Regional Head Election of Kudus Regency in 2018 had importance to observe. Applying qualitative approach this research try to reveal the supporting factors underlying the participative behavior in the election. It was found in the research that: Firstly, the sociological factors, such as discussion, family opinion, organizational relations, friendship interaction, working sphere, religion, and gender of the candidates; Secondly, psychological factors, which refer more to identify the candidate identities as well as the party supporters; and thirdly, rational factors, in which voters understand the vision, mission, and the program of the candidates